2022
DOI: 10.1111/jen.12977
|View full text |Cite
|
Sign up to set email alerts
|

Are invasive species promoting yellowjacket invasion in Patagonia?

Abstract: In recent decades, yellowjacket wasps, including Vespula vulgaris, have successfully been established in Patagonia. Additionally, the invasive willow Salix fragilis has also invaded areas next to watercourses, which in turn are typically colonized by the giant willow aphid (GWA, Tuberolagnus salignus), another invasive species. The honeydew exuded by the aphids has been reported to be used as a carbohydrate source by this social wasp. Our aim was to determine whether willows and GWA (invasive complex) on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Nevertheless, factors such as the coinciding seasonality, the high volumes produced and predictability of its location/ease of access could translate into an important driver for vespid colony success. The effect was suggested in a recent study conducted in the area looking at V. vulgaris nest size and distribution, and found that habitats close (< 200 m) to stream margins, where Salix fragilis and GWA occur, contain higher nest densities with larger individuals 23 . It is important to note that our sampling protocol did not distinguish between the two yellowjacket species present in Patagonia, since identification is difficult to be carried out on non‐stationary individuals.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Nevertheless, factors such as the coinciding seasonality, the high volumes produced and predictability of its location/ease of access could translate into an important driver for vespid colony success. The effect was suggested in a recent study conducted in the area looking at V. vulgaris nest size and distribution, and found that habitats close (< 200 m) to stream margins, where Salix fragilis and GWA occur, contain higher nest densities with larger individuals 23 . It is important to note that our sampling protocol did not distinguish between the two yellowjacket species present in Patagonia, since identification is difficult to be carried out on non‐stationary individuals.…”
Section: Discussionmentioning
confidence: 92%
“…forests are not infested with hemipterans and wasps do not reach the high densities observed in New Zealand 28 . However, a recent study suggested that yellowjackets may be favored by GWA as V. vulgaris nest size and density in habitats close (< 200 m) to stream margins, where Salix fragilis and GWA occur, are higher and produce larger individuals than in sites without willows and aphid 23 . It is important to note that GWA and Vespula spp.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations